2021
DOI: 10.4103/0972-6748.328813
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smartphone addiction and its relation with sleep disturbance and low self- esteem among medical college students

Abstract: Background: Use of smartphone is on the increase worldwide. They have revolutionized our lives to an extent that was unimaginable before the pandemic. Excessive use of smartphones reaching the levels of potential addiction among medical students and its relation to individual's sleep quality and self-esteem led us to study this prevalence. Aim: This stuay aimed to study the prevalence of smartphone addiction and its relation with self-esteem and sleep d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous research has examined excessive smartphone use among nursing and health students. The review findings indicated that studies have been conducted in Spain (Aguilera-Manrique et al, 2018;Gutiérrez-Puertas et al, 2019), Pakistan (Javaid et al, 2019), Saudi Arabia (Alhazmi et al, 2018;Alkhateeb et al, 2020;Venkatesh et al, 2016), Iran (Miri et al, 2019;Mohammadi et al, 2018), Oman (Siddiqi et al, 2017), India (Bartwal & Nath, 2020;Basu et al, 2018;Dhamija et al, 2021;Jahagirdar et al, 2021), Thailand (Boonluksiri, 2018;Tangmunkongvorakul et al, 2019), Turkey (Cerit et al, 2018), China (Chen et al, 2017;Song et al, 2022;Wang et al, 2021;Zhou et al, 2022), the United States (Brubaker & Beverly, 2020), South Korea (Sok et al, 2019), Malaysia (Lei et al, 2020), and Indonesia (Hanafi et al, 2019). The studies' samples included students of medicine, dentistry, nursing, physiotherapy, and other health sciences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has examined excessive smartphone use among nursing and health students. The review findings indicated that studies have been conducted in Spain (Aguilera-Manrique et al, 2018;Gutiérrez-Puertas et al, 2019), Pakistan (Javaid et al, 2019), Saudi Arabia (Alhazmi et al, 2018;Alkhateeb et al, 2020;Venkatesh et al, 2016), Iran (Miri et al, 2019;Mohammadi et al, 2018), Oman (Siddiqi et al, 2017), India (Bartwal & Nath, 2020;Basu et al, 2018;Dhamija et al, 2021;Jahagirdar et al, 2021), Thailand (Boonluksiri, 2018;Tangmunkongvorakul et al, 2019), Turkey (Cerit et al, 2018), China (Chen et al, 2017;Song et al, 2022;Wang et al, 2021;Zhou et al, 2022), the United States (Brubaker & Beverly, 2020), South Korea (Sok et al, 2019), Malaysia (Lei et al, 2020), and Indonesia (Hanafi et al, 2019). The studies' samples included students of medicine, dentistry, nursing, physiotherapy, and other health sciences.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in India by Jahagirdar et al (2021) reported that the prevalence of smartphone addiction among medical students was 81.1%. Findings from the same country indicated that 33.3% of women and 46.1% of men experienced smartphone addiction (Chatterjee & Kar, 2021), with a prevalence of 52% (Dhamija et al, 2021). Lei et al (2020) also reported that 40.6% of medical students in Malaysia experienced smartphone addiction, with men having higher rates of addiction than women.…”
Section: Prevalence Of Smartphone Users and Addiction Among Nursing A...mentioning
confidence: 95%
“…Metacognition is a multifaceted concept that is broadly defined (in the psychopathology arena) as knowledge of mental activities ('metacognitions') and strategies for appraising, monitoring, and regulating cognition, which can include worry, rumination, thought suppression and threat monitoring, for example (20). Two levels of sleep-related arousal involve metacognition and cognition processes.…”
Section: Introductionmentioning
confidence: 99%